Penerapan Metode Weighted Product (WP) Pada Pemilihan Supplier Kimia Terbaik PT. Mayer Indah Indonesia Bogor - Anisah Fitriyani; Rachman Komarudin; Yana Iqbal Maulana; Ali Haidir (LPPM Universitas Bina Sarana Informatika, 2020)
PT. Mayer Indah Indonesia is a company engaged in the field of textile. In order to face business competition, there are several problems that often arise, namely not having supplier selection procedures. The supplier selection conducted by the company's purchasing department at this time is a direct survey and price comparison. supplier distance with the company so that shipping costs are high and ease of negotiation and payment systems. So the supplier selection needs to be done by using the right method in accordance with company standards, namely weighted product (wp) with the aim of providing information to companies about alternative methods that can be used in objectively selecting suppliers and providing input on the performance of suppliers. Keywords: Selection, Chemical Supplier, Best, Weighted Product.